Chemometric Analysis of Phytochemical Content and Antioxidant Activity of Ethanol Extract 70% and Ethyl Acetate of Kersen Leaf (Muntingia calabura L.) - Afif Putri Habibah; Endang Setyowati; Emma Jayanti Besan (Lembaga Pengembangan Kinerja Dosen, 2025)
This study analyzed the phytochemical content and antioxidant activity of kersen leaf extract (Muntingia calabura L.) obtained with 70 % ethanol and ethyl acetate through a chemometric approach. Extraction is carried out by maceration, total flavonoids are determined by UV-Vis spectrophotometry with quercetin, while total phenolics with gallic acid. Antioxidant activity was tested using the DPPH method and the IC₅₀ value was calculated. The results showed that the total flavonoid content in 70% ethanol extract was 3.374 ± 0.082 mg EK/mL, while in ethyl acetate extract it was 2.726 ± 0.014 mg EK/mL. The total phenolic content in 70% ethanol extract was 152.34 ± 5.71 mg EAG/mL, while in ethyl acetate extract it was 262.78 ± 6.27 mg EAG/mL. The highest antioxidant activity was obtained from ethyl acetate extract with an IC₅₀ value of 34.45 ± 1.23 μg/mL, while ethanol extract 70% showed an IC₅₀ value of 42.35 ± 7.22 μg/mL. Chemometric analysis using Principal Component Analysis (PCA) showed a relationship between the 70% ethanol flavonoid content and ethyl acetate on the antioxidant activity of the DPPH method.